1998
DOI: 10.1016/s0022-5347(01)63229-4
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Localized Untreated Prostate Cancer Based on 791 Men Treated Only With Radical Prostatectomy: Common Ground for Therapeutic Trials and TNM Subgroups

Abstract: T1c cancers are similar to T2a cancers in tumor volume and percent Gleason grade 4/5, the primary determinants of therapeutic failure. Minimal 5-year cure rates for T1c and T2a cancers are similar. Transition zone cancers are 2.5 times more common in T1c cancers than in palpable T2 tumors. T2a cancers like T1c cancers are highly favorable tumors and should be retained in TNM classifications. These data suggest that the 4 clinical stages of T1c to T2c can serve as a valid basis for comparing different therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 13 publications
0
36
0
2
Order By: Relevance
“…In contrast, TZ tumors can frequently be missed on biopsy and are often discovered in TURP specimens [44]. Initial studies looking at the impact of zonal tumor origin indicated a much more indolent nature, with TZ tumors demonstrating an 81% 5-year cure rate, relative to 53% seen in PZ tumors [45]. In a series by Noguchi et al [46], TZ tumors demonstrated a biochemical recurrence-free rate of 71.5% versus 49.2% for PZ cancers.…”
Section: Anatomical Zonal Considerationmentioning
confidence: 99%
“…In contrast, TZ tumors can frequently be missed on biopsy and are often discovered in TURP specimens [44]. Initial studies looking at the impact of zonal tumor origin indicated a much more indolent nature, with TZ tumors demonstrating an 81% 5-year cure rate, relative to 53% seen in PZ tumors [45]. In a series by Noguchi et al [46], TZ tumors demonstrated a biochemical recurrence-free rate of 71.5% versus 49.2% for PZ cancers.…”
Section: Anatomical Zonal Considerationmentioning
confidence: 99%
“…Thus, 217 men (57%) had favorable T1c and T2a clinical stages. 14 The median age was 65 years ( Table 1). Sixty of 379 men were older than 71 years; 60% had no biochemical evidence of disease recurrence, which was the same as that for the whole group of 379 men (62%).…”
Section: Series Characteristicsmentioning
confidence: 99%
“…These ranges are sufficiently broad that it should be possible with further research to estimate them. The area of cancer in each biopsy core specimen, number of positive findings in core specimens of 6 to 10 systematic biopsies of the prostate, serum PSA level (half of which is related to cancer volume 16 ), and clinical stage from digital rectal examination 14 are all related to cancer volume and should be part of any future algorithm for estimating cancer volume preoperatively. Although the analysis in this article of morphologic variables that determine failure is based on treatment only by radical prostatectomy, cancer volume and the % Gleason grade 4/5 cancer in peripheral zone cancers are so powerful that it is highly likely the results of any other therapeutic modality, such as radiation or chemotherapy, will be determined by the same morphologic variables described in this research.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant positive correlations existed between T 2 and ADC for PZ, TZ, PZ and TZ together, but not T 2 weighted (T 2 W) MRI is routinely used for diagnosis and staging of prostate cancer, because the soft-tissue contrast is able to identify hypointense tumours within the high signal intensity of the normal glandular peripheral zone [PZ [1,2]; where the majority (;70%) of prostate cancers occur [3]]. It is less useful at distinguishing hypointense tumours in the transition zone (TZ) because of the low signal intensity of stromal and glandular hyperplasia on T 2 W images.…”
mentioning
confidence: 99%